'Myth-makers to eternity': the idea of the poetic drama in England, 1897-1928 - Longworth, K (2023)
This thesis examines a largely occluded and misunderstood movement in early twentieth century cultural history, when a significant number of poets and critics made repeated calls for the revival of ‘poetic drama,’ not as a coterie form, but as a viable alternative to the commercial theatre of their time. Throughout this period, writers including Stephen Phillips, Gordon Bottomley, John Drinkwater, Wilfrid Gibson, Lascelles Abercrombie and, ultimately, T.S. Eliot persistently delineated what they perceived as the need to restore to the theatre what had once been its more lofty functions. The theatre was a place where the real, it was suggested, could and should meet the ideal and renew the status of art as a crucial correspondence to an unassailable and timeless truth, restoring the ties of a fractured community.